An Assessment of Banking Performance: The Balanced Scorecard Approach - Evi Octavia; Ait Novatiani; Rima Rachmawati; Che Rosmawati Che Mat (Universitas Pendidikan Ganesha, 2024)
There is a need to explore the effectiveness and comprehensive implementation of the Balanced Scorecard in improving banking performance, particularly considering the unique challenges of regulatory influence and sector-specific dynamics. This research aims to measure the performance of Bank Panin, which is motivated by a decline in net profit, profit before tax, and negative third-party funds. The study employs a Descriptive Qualitative approach using Balanced Scorecard measurements. The research focuses on four perspectives: 1) learning and growth, 2) customer, 3) internal business processes, and 4) financial. Data collection for these perspectives utilized a questionnaire method with a Likert scale, with data validity confirmed through validity and reliability tests. The results indicate that customer satisfaction at Panin Bank Tbk Bandung Branch is favorable. In terms of internal business processes, Panin Bank offers comprehensive products/services, a widespread office network, innovative products, and high-quality customer service. From the growth and learning perspective, employee productivity is satisfactory. Financially, metrics such as the Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), and Return on Assets (ROA) meet excellent criteria. This study highlights the significant role of banks in creating employment, enhancing human resource skills, and supporting the local economy. The robust financial performance of banks not only stabilizes the sector but also facilitates credit availability for small businesses, thereby promoting economic growth in communities.